2006
DOI: 10.1002/ajmg.c.30113
|View full text |Cite
|
Sign up to set email alerts
|

Through the viewfinder: Positive Exposure a year later

Abstract: Positive Exposure, a non-profit organization founded and directed by former fashion photographer Rick Guidotti and co-directed by psychiatrist Dr. Diane McLean, uses photography and video interviews to explore the lived experiences of people affected with genetic conditions. Positive Exposure challenges pervasive social biases and stereotypes about genetic variation and strives to broaden and enrich societal perceptions of human beauty and spirit. Presented here are the open-ended personal reflections complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The background of each photograph was variable depending on the venue of the session. Each session lasted approximately 30 min and hundreds of photographs were taken of each participant [see Sutton et al, 2006 p. 262 for additional information on PE photo‐shoots].…”
Section: Methodsmentioning
confidence: 99%
“…The background of each photograph was variable depending on the venue of the session. Each session lasted approximately 30 min and hundreds of photographs were taken of each participant [see Sutton et al, 2006 p. 262 for additional information on PE photo‐shoots].…”
Section: Methodsmentioning
confidence: 99%
“…This is a secondary data analysis from a study entitled Photographic and Video Experience (PAVE) that sought to explore the impact of Positive Exposure (PE)—a nonprofit organization that uses photography and videography to challenge social prejudices around genetic variation—on individuals with CFCs (Sutton et al, 2006; Loewenstein et al, 2008). PAVE interviews revealed that participants consistently initiated discussions about their experiences—positive and negative—with reconstructive surgery.…”
mentioning
confidence: 99%
“…The participant [was] not posed but [was] encouraged to be spontaneous and relaxed, even to move around and laugh, depending on how they [were] feeling." 5 Participants were surveyed and interviewed on personal topics such as self-perception, perception of how others perceive them, and their feelings toward photography, and were asked to describe their experience and feelings and reactions immediately following and 1 year after the professional photoshoot.…”
Section: Part Ii-why Does Mitigating the Clinical Gaze Matter?mentioning
confidence: 99%
“…One participant reported that, a year after the photoshoot, he was still able to "see himself in a new light," while another reported that she "discovered that she can now see the beauty in herself." 5 In fact, the "4 participants described how their newfound self-perceptions as attractive and confident individuals persist[ed] [for] more than a year after their Positive Exposure photo-shoot experience." 5 While the study size was small, it was clear that treating the participant as a unique subject through this photoshoot, a medium which existed previously as a means of objectification but now manifested itself as an avenue of self-expression, helped the participants embrace themselves beyond the physical and move toward a healthier, more authentic selfimage.…”
Section: Part Ii-why Does Mitigating the Clinical Gaze Matter?mentioning
confidence: 99%